Effects of a compassion-based program on the grief experienced by caregivers of people suffering from dementia: a randomized controlled clinical trial - Leila Jahani; Shahla Abolhassani; Sima Babaee; Victoria Omranifard (BMC Nursing, 2022)
Abstract Background Dementia is a syndrome that reduces the cognitive and functional abilities of the brain increasing the need for care. The caregivers of these patients are mostly their family members. The great care burden causes devastating effects on the health of family caregivers and the grief experienced by these family caregivers is considerable. This study was conducted to investigate the effects of a compassion-based program on the grief experienced by caregivers of people suffering from dementia. Method The present study was a randomized controlled clinical trial in which 70 family caregivers of people suffering from dementia were sampled through the block method and they were divided into experimental and control groups. The data collection tools included demographic information questionnaire and grief inventory that was completed before, a week and a month after the implementation of the compassion-based program in five sessions virtually by sending offline content to the experimental group. The obtained data were analyzed by SPSS 22 software using the repeated measures analysis of variance. Results The mean comparison of scores of the grief experienced in the experimental group between pretest and posttest and follow-up, unlike the control group, showed a significant difference (p < 0.001). The mean scores of the experimental and the control groups were significantly different in terms of experiencing mourning and all of its fields (p < 0.001). The mean comparison of post-test and follow-up showed that the effect of a compassion-based program at the follow-up stage has been mitigated. Conclusions According to the study results, the compassion-based program reduced the grief experienced by the family caregivers of people suffering from dementia. Nevertheless, the effect of a compassion-based program has been reduced over time. This program can be a good guide for providing society-oriented services to the health team. Trial registration This study is registered by Iranian Registry of Clinical Trials with decree code: IRCT20190712044181N4  on 02/06/2020.